Star Restaurant / Noriajazimah Mokhtar... [et al.] - Mokthar, Noriajazimah; Draman, Siti Sara; Md. Bashah, Norasidah; Mat Hussin, Noraida; Hasan, Noraini (2003)
Asean Food Restaurant is a partnership business incorporated by five members. Our business will be located at Lot 211, Medan Putra, Seberang Jalan Putra, 05150 Alor Setar, Kedah Darul Aman. The operation of our business will start on 19 January 2003. The main operation of our business is to serve various types of Asean foods. We choose to form a business of Asean food restaurant because there are various types of Asean meals that can be commercialized to Malaysia citizen. Additionally Asean foods are unique and capable to attract people to taste. Asean food Restaurant is expecting to have customers from local people in Alor Setar, people from other states and foreignness who are visiting Malaysia, Asean Food Restaurant has its own concept and identity differ from restaurant because it serves Asean foods and meals at affordable price. We are sure that our customer will be satisfied Beside to satisfy our customers need, we era also want to gain profit from our business